The role of social studies curricula in enhancing the concept of national belonging among students from the perspective of teachers in the northern Governorates of the West Bank - Sleem, Hiba Khaled (Journal of Educational and Psychological Sciences, 2020)
This study aims at identifying the role of social studies curricula in enhancing the concept of national belonging among students from the perspective of teachers in the northern Governorates of the West Bank. The analytical descriptive method is used in the study. Moreover, a questionnaire has been distributed randomly to 100 of the social studies teachers in the northern Governorates of the West Bank. The results of the questionnaire have been compiled, encoded and processed statistically using the program of Statistical Package for the Social Sciences (SPSS). The results of the study show that the role of social studies curricula in enhancing the national belonging among students, from the perspective of social studies teachers, were weak according to the arithmetic average that has reached (2.25). Furthermore, the results indicate that there have been no differences in the views of teachers, regarding the topic of the social studies curricula, depending on the various variables such as sex, place of residence, academic qualification, and years of experience. The researcher recommends strengthening the national belonging by activating volunteering among students, celebrating national events inside and outside the school, and creating awareness of the national events within the students by transforming national days from ordinary days to occasions commemorated by them, in addition to acquiring media coverage. Consequently, there is a strong necessity to prepare pre-service teachers and train them for teaching in order to be able to raise students’ awareness of the national belonging. In addition, graduate students will become more enlightened and thoughtful.